(untitled) (Jóvenes en la Ciencia, 2026)
Amaranthus hybridus L., known locally in Salvatierra, Guanajuato, as quelite lero, is a species of high nutritional and medicinal value. It is traditionally used to relieve gastrointestinal disorders and prevent chronic diseases such as cancer. However, its use has declined due to the modernization of consumption habits, the preference for ultra-processed foods, the contamination of its edible portion by irrigation water or agrochemicals, and the progressive loss of traditional knowledge. Currently, this plant is often considered a weed in both agricultural systems and urban areas, which has contributed to its devaluation. This study analyzed the dietary behavior of rural residents in the municipality of Salvatierra, identifying the degree of preservation of inherited knowledge about the consumption and use of quelite lero. Through a bibliographic review and community interviews, it was found that older adults, especially women, are the main bearers and transmitters of traditional practices, maintaining their culinary and medicinal use. It was estimated that the revaluation of this plant could represent economic savings of up to 40% in the prevention and treatment of conditions such as anemia and digestive disorders, and, in the case of cancer, 20% in complementary care. It is concluded that recovering traditional knowledge about the use of quelite lero not only strengthens local cultural and food identity but can also contribute to improving public health and reducing family costs associated with chronic diseases.